RECOMMENDATIONS TO IMPROVE EMPLOYEE PERSONAL ATTITUDE TOWARD REPORTING PATIENT SAFETY INCIDENTS - Andari, Purwo; Handriyanto, Candra Ferdian; Damayanti, Nyoman Anita; Pudjirahardjo, Widodo Jatim (Universitas Airlangga, 2024)
Background: Patient Safety Incidents (PSI) in hospitals are adverse events that need to be reported for effective identification and risk management, aiming to prevent reoccurrence of incidents. However, not all incidents are documented, as evidenced by the discrepancy in the number of phlebitis reported by employees as well as Infection IPCLN at three hospitals. Aims: Provide recommendations to improve employee Personal Attitude towards reporting PSI at three hospitals owned by Company A. Methods: The method adopted was a cross-sectional research design; data were collected from three hospitals owned by company A and tested using multiple logistic regression statistics tests. Data on Phlebitis reported from January to July 2018 at three hospitals owned by Company A was used. Furthermore,135 respondents were taken from the service installations of the three hospitals. The Lameshow formula and proportional random sampling are applied to determine the sample. Results: The variables of error orientation (p = 0.001; β = 0.349), behavioral belief (p = 0.008; β = 0.234), and perceived behavioral control (p = 0.003; β = 0.222) had a positive and significant effect on the personal attitude of employees reporting PSI. Conclusion: Two approaches were recommended to improve the personal attitude of employees in reporting PSI. Keywords: Hospital, Patient safety incidents, Personal attitude, Underreporting